Gender-inclusive development through fintech: Studying gender-based digital financial inclusion in a cross-economy setting - Sabyasachi Tripathi; Meenakshi Rajeev (Asian Development Bank Institute (ADBI), 2023)
Financial inclusion (FI) for vulnerable populations, such as women, is critical for achieving gender equality, women's empowerment, and thereby inclusive growth. In this regard, the use of digital financial services is of particular significance for women as it allows them easier access to financial products for business and household needs. For implementing policies to reduce the financial exclusion of women, it is necessary to first measure the extent of FI in a society. While there have been several attempts to measure FI for the general population, there is limited literature on gender-based measurement of FI. This paper fills this important research gap by developing a gender-based FI index (GFII) focusing particularly on digital services and evaluating the performance of economies across the globe (by considering 109 economies based on data availability) in terms of a gender-based FI measure developed by us. This index has been developed using two separate indices, a digital financial service index (DFI) and a conventional financial service uses index (CFI). One contribution of the paper is to relate the Gender Development Index (GDI) and the Gender Inequality Index (GII) of economies, two well-known measures of inclusive development, with the GFII and the DFI for females (DFIF). This exercise shows that while there is a positive correlation between these two sets of indicators, there are a number of economies that are high (or low) in gender development (or inequality),which need to improve their digital FI. Interestingly, using the Global Findex database and the Feasible Generalized Least Squares (FGLS) and instrumental variable panel data model, we show that health, education, the labor force participation rate, and political empowerment of women significantly impact the digital financial inclusion of women. The paper makes relevant policy suggestions for improving women's digital financial access and thereby enhancing gender empowerment for faster and more inclusive growth.
Keywords: G2; G20; P34; 330; digital financial inclusion; gender-based financial inclusion; inclusive growth; gender development index